Penerapan Media Audio Visual Untuk Meningkatkan Minat Belajar Siswa Pada Pembelajaran Daring Sejarah Kebudayaan Islam - Rohmah, Siti; Syifa, Mar’atus (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2021)
Lack of interest in learning in class IVB SKI learning at MIS Nurul Hikmah which only uses the recitation method so it is necessary to apply audio-visual media to increase student interest in online learning. This study aims to describe: the process of applying audio-visual media to SKI online learning, and increasing interest in learning in the application of audio-visual media to SKI online learning. This research uses descriptive qualitative research and the type of case study research to find out a case to be studied in depth and described in detail. Collecting data through observation, interviews and documentation. Technical data analysis consists of data collection, data reduction, data presentation and conclusions. The results of this study indicate that: (1) the process of implementing audio-visual media in SKI online learning through WhatsApp includes planning, implementation with opening, core and closing activities. Then the learning process is in the form of video slides (images, sound and writing), voice notes, documents in the form of word/pdf and calls. (2) an increase in student interest in learning can be seen from the number of responses from students in the group during absences, the emergence of a sense of pleasure in learning, the presence of attention, active in doing and collecting assignments and obeying the rules that have been set, this is in accordance with the indicators of interest